Music and singing in pakistan: are they allowed in islam? - Ghazali, Ali (Islamic book Service; S.l., 2010)
Are music and singing allowed in Islam If the answer is a definite yes or no then why has the question of its lawfulness become the subject of debate among Muslim scholars for centuries. In this treatise translated from the eighteenth book of Ihya Ulum Al-Din, readers get an insight into the pros and cons of the controversy and are guided by the greatest authority of traditional Islam none other than Iman Al Ghazali. For Al Ghazali, it is important to have true knowledge to reap the benefit of music. Those who have no sufficient knowledge of God and His attributes, he writes, are liable to apply what they hear both to what is allowable and what is not.